G388(P) Atypically typical!. (May 2019) - Coates, S; Vallabhaneni, P
Abstract : Background: This is a report on 3 cases of Atypical Kawasaki Disease (AK), all infants aged <6 months presenting to a district general hospital within a 6 month period. AK is difficult to diagnose due to the incomplete presentation of the diagnostic criteria as shown in the following cases. Results: Case 1: a 17 week old female with a repaired ALCAPA presented with a 1 day history of agitation, fever, and decreased feeding and urine output. The fever persisted for 5 days, and given the presence of an aseptic inflammatory pattern, rash, and ECHO findings, AK was considered. Case 2: a 14 week old female presented with fever, cough, generalised maculopapular rash, non–exudative conjunctivitis, erythematous pharynx and lips, and left–sided lymphadenopathy. AK was considered, although ECHO findings were normal. Case 3: a 11 week old Asian female presented with 2 day history of erythema and inflammation around a previously normal BCG scar; fever, red conjunctiva, tachycardia and vomiting were also present. Over the following 4 days there was a rise in both the lactate and CRP, the fever and tachycardia increased, and blanching papules on the legs and trunk developed. PUO and enterovirus meningitis were considered, but after a negative CSF PCR and the development of swollen hands and feet on day 5 of fever, AK was considered and treatment was initiated. Conclusion: AK is less common than sepsis, but is still an important differential diagnosis in at-risk age groups as it is associated with increased risk of developing coronary artery aneurysms. We would like to raise awareness amongst paediatricians to consider AK as a differential diagnosis in children less than six months old with no clear focus of infection.